Greenland's Winter Whales: The Beluga, the Narwhal and the Bowhead Whale - Higdon, Jeff W. (Arctic, 2007)
Few people would be as qualified as these authors to write a book on Greenland's whales. Over the past decade, Drs. Heide-Jørgensen and Laidre have published extensively on the cetaceans of West Greenland and the eastern Canadian Arctic, and these studies form the basis for this book. The subject matter covers three species of Arctic whales: the beluga whale (Delphinapterus leucas), the narwhal (Monodon monoceros), and the bowhead whale (Balaena mysticetus). Around 15 species are found in Greenland waters; however, most are present in summer months only. The authors coin the term "winter whale" to refer to the three species that occur in Greenland during the winter months. The authors' stated objective was to provide a popular description of the state of knowledge about the three species in Greenland, their importance to Greenland and Greenlanders, and their role in the Arctic ecosystem. The book fulfills these objectives, providing a readable and thorough summary of the three whale species in Greenland. The geographic focus is mainly limited to West Greenland, for two reasons. First, this is where the majority of research has taken place, and second, all three species occur on this side of the country. The book finishes with sections on the management history and current status of the three whale species and suggests important directions for future research. There has been a long history of exploitation, and unfortunately overexploitation, of all three species in Greenland. Bowhead numbers have rebounded following near extermination at the hands of commercial whalers up until the early 1900s. The situation for both narwhals and belugas in West Greenland is considerably direr. Both species have been overharvested in West Greenland in recent years, and populations have declined significantly. Greenland's wildlife management practices have received a large amount of negative attention and criticism in recent years (e.g., Hansen, 2002). Greenland's Winter Whales ends with a plea for Greenlanders to practice sustainable management and improve this negative perception. It remains to be seen whether Greenlanders will follow these suggestions and improve their wildlife management practices.